Implementasi Kebijakan Intervensi Gizi Spesifik sebagai Upaya Penanganan Stunting di Kabupaten Malang - Maulana, Ilham Nur Hanifan; Sholihah, Qomariyatus; Wike, Wike (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2022)
This study explain the implementation of spesific nutrition intervention policy in attempt of stunting handling refer to Malang Regent Act No. 33 of 2018 about Stunting Prevention Efforts. A qualitative-descriptive approach used to describe the policy implementation according to A Model of The Policy Implementation Process by Donald Van Meter and Carl Van Horn. Amid of COVID-19 pandemic, several spesific nutrition activities were not carried out due to health budget refocusing. However, the proponent of implement agent such as nutritionist officer in Puskesmas and village tocologist are the key actors in pursuance of stunting integration action timeline. In adaption to this situation, home visits and appointments are made to reach a wider target group. The need for technical regulations as a continuity of Malang Regent Act No. 33 of 2018 to accomodate the handling of stunting through spesific nutrition intervention during the time of pandemic optimally.